The Level of Lay Up Shoot Ability of Female Athletes of Extracurricular Basketball SMA N 1 Bengkulu Tengah School Year 2023/2024 - Hidayat, Ilham; Perdima, Feby Elra; Martiani (Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine how the level of ability to Lay Up Extracurricular Women's SMAN 1 in the City of Bengkulu in the academic year 2019/2020. The research method used was a survey using tests. The population was 20 female students and the sample in this study used saturated sampling, namely all female students of the extracurricular Bolabasket SMAN 1 Bengkulu City as many as 20 female students. Data collection method used in this study is a survey method with one shot method approach. The data analysis technique used is descriptive statistics percentage. The most lay-up shoot test results are in the medium category with an average of 12.8. The ability to shoot up shoot athletes in the basketball 1 MAN basketball extracurricular city in Bengkulu which is categorized as very high is 2 people (10%), high category is 2 people (10%), and the medium category is 8 people (40%), and the low category is 8 people (40%), and the very low category is 0 people (0%). The overall conclusion is in the quite good category.